Interest rate risk management and Islamic Banking: Evidence from Malaysia - Khaliq, Ahmad; Mohd Thas Thaker, Hassanudin; Mohd Thas Thaker, Mohd Asmy; Pitchay, Anwar Allah (IIUM Institute of Islamic Banking and Finance, 2017)
The fluctuation of interest rate in the market has let the Islamic banks becoming more cautious and taking a step ahead in managing good risk management practices. This is an important element when a country adapts a dual banking system. The interest rate is obviously prohibited in Islam; however, it does not mean that the Islamic banks will not encounter any risk due to the interest rate fluctuation in the market. This is due to the nature of the Islamic banking balance sheet where it is fixed on asset side whereas in the conventional banking it looks more flexible to the asset, thus putting the Islamic banks unable to react expeditiously to the fluctuation in market interest rate which later leads to greater exposure to the rate of return risk. Therefore, the present study aims to investigate the effect of the interest rate risk towards the portfolios of the Islamic banks operating in the Malaysia. The quantitative result reveals that the majority of the Islamic banks are exposed to the interest rate risk and it is explained by the financial and economic variables. This study is expected to add value to the existing literature in risk management by proposing policy recommendations and methodological innovation.